Adjunctive use of a nanocolloidal silver-based local antiseptic solution in the nonsurgical treatment of periodontitis: A split-mouth clinical study - Sofia Iozon (Ene); Darian Rusu; Andreea Ciurea; Iulia Cristina Micu; Calin Latiu; Alexandra Roman; Andrada Soanca (Amaltea Medical Publishing House, 2023)
Objectives. The aim of the present study was to evaluate the potential additional clinical benefit of a commercial nanocolloidal silver-based local antiseptic used as irrigation solution after subgingival mechanical instrumentation. Material and methods. Periodontitis patients were treated following the current guidelines. Two randomly assigned hemiarches of each patient received subgingival mechanical instrumentation plus irrigations with the commercial product (experimental group); the other two hemiarches received mechanical instrumentation plus saline irrigations (control group). A clinical periodontal examination at baseline moment and after 3 months was performed. The parameters considered for analysis were oral hygiene index (IHI), bleeding on probing score (BoP), periodontal pocket probing depth (PD), gingival recession (GR) and clinical attachment level (CAL). 72 sites were included in the analysis, the site with the highest PD/quadrant for each patient. Data were analyzed using GraphPad Prism version 8.0.1 (GraphPad Software Inc., La Jolla, CA, USA). p<0.05 was set as statistical significance level. Outcomes. Eighteen periodontitis patients were treated. All clinical parameters improved at re-evaluation, compared to baseline, both in experimental and control group. The differences were statistically significant in terms of IHI, BoP and PD reduction. At re-evaluation, there were no statistically significant differences between periodontal parameters registered in the experimental and control sites. Conclusions. The present study failed to prove an adjunctive clinical benefit of the antiseptic product in the nonsurgical treatment of periodontitis. These results support the gold standard role of subgingival mechanical instrumentation in the periodontitis' therapeutic protocol.